2021
DOI: 10.1021/acsanm.1c00558
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of CsPbBr3 Νanocrystals for Photonic Applications

Abstract: The primary obstacle to the use of lead halide perovskite nanocrystals (NCs) in optoelectronics is the inability of traditional ligand engineering approaches to provide robust surface passivation. The structural lability can be mitigated by employing different ligands such as long-chain quaternary ammonium and zwitterionic surfactants. Here, we report a comprehensive study that probes the impact of such surface passivation routes on the optoelectronic properties of weakly confined CsPbBr 3 NCs. Spectroscopy un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Lead halide perovskites with the APbX 3 (X = Cl, Br, I) structure with organic (e.g., methylammonium (MA + ) or formamidinium (FA + )) or inorganic (Cs + ) A-site cations have emerged as promising candidates for various optoelectronic applications ranging from photovoltaics , to X-ray and γ-detectors, light-emitting devices (LEDs), lasers, , and quantum light sources. , Most notably, colloidal perovskite quantum dots (QDs) have demonstrated outstanding suitability for display applications with near-unity photoluminescence quantum yields (PLQY), excellent long-term stability, and narrow emission at room temperature, as well as beneficial properties for quantum emitters with long exciton coherence times and ultrafast emission at cryogenic temperatures. , Size engineering of such structures recently allowed the formation of highly anisotropic CsPbBr 3 nanoplatelets (NPLs), introducing strong asymmetric quantum confinement and emission colors in the turquoise/blue spectral range, while maintaining high quantum yields and stability. …”
mentioning
confidence: 99%
“…Lead halide perovskites with the APbX 3 (X = Cl, Br, I) structure with organic (e.g., methylammonium (MA + ) or formamidinium (FA + )) or inorganic (Cs + ) A-site cations have emerged as promising candidates for various optoelectronic applications ranging from photovoltaics , to X-ray and γ-detectors, light-emitting devices (LEDs), lasers, , and quantum light sources. , Most notably, colloidal perovskite quantum dots (QDs) have demonstrated outstanding suitability for display applications with near-unity photoluminescence quantum yields (PLQY), excellent long-term stability, and narrow emission at room temperature, as well as beneficial properties for quantum emitters with long exciton coherence times and ultrafast emission at cryogenic temperatures. , Size engineering of such structures recently allowed the formation of highly anisotropic CsPbBr 3 nanoplatelets (NPLs), introducing strong asymmetric quantum confinement and emission colors in the turquoise/blue spectral range, while maintaining high quantum yields and stability. …”
mentioning
confidence: 99%
“…The figure also contains images of the NC-sensitized membranes under ambient and UV-light conditions, demonstrating their good uniformity, optical quality, and bright emission. Green emitting CsPbBr 3 NCs with dimethyldioctadecylammonium bromide (DDAB) ligands have been selected as the active gain media, owing to their structural robustness and good photostability combined with exceptionally high photoluminescence (PL) QY approaching in the liquid phase 100% (larger than 90% in the solid state) . The NCs employed were cuboids with mean sizes of ∼10 nm, as presented in the TEM images of Figure S1, centered at ∼2.40 eV with a full width half maximum (fwhm) of ∼80 meV, as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Green emitting CsPbBr 3 NCs with dimethyldioctadecylammonium bromide (DDAB) ligands have been selected as the active gain media, owing to their structural robustness and good photostability combined with exceptionally high photoluminescence (PL) QY approaching in the liquid phase 100% (larger than 90% in the solid state). 26 The NCs employed were cuboids with mean sizes of ∼10 nm, as presented in the TEM images of Figure S1, centered at ∼2.40 eV with a full width half maximum (fwhm) of ∼80 meV, as shown in Figure 1b. For the red-emitting active gain media, CsPb(Br,I) 3 NCs with variable bromine-iodine ratio were obtained via a newly designed synthesis using hot-injection methodology with oleic acid (OA) and two different branched ligands such as dioctylamine (DOAm) and DDAB.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[34] Manoli et al reported a modulation effect on CPC by using different ligands. [35] There is still a lack of insight into the effects of commonly used organic ligands on the CPC in CsPbX 3 NCs; despite this being of universal significance in further practical applications. The underlying mechanism is even far less discussed.…”
Section: Introductionmentioning
confidence: 99%